AMPLIFIKASI DAN IDENTIFIKASI MUTASI PADA FRAGMEN 0,5 KB GEN rpoB ISOLAT 134 Mycobacterium tuberculosis MULTIDRUG RESISTANT DENGAN METODE NESTED POLYMERASE CHAIN REACTION - Made Dharmesti Wijaya; I Nengah Wirajana; Sagung Chandra Yowani (Jurnal Kimia (Journal of Chemistry), 2014)
Research has been conducted to amplify and identify mutations in the rpoB gene fragment, 0,5 kb, from the isolate 134 Mycobacterium tuberculosis multidrug resistance (MDR). Amplification was performed using the method nested polymerase chain reaction (nested PCR) while sequencing was conducted in one direction using forward inner primer. Nucleotide sequence obtained was translated into amino acids using MEGA4 program. Amplification of M.tuberculosis rpoB gene fragment, 0,5 kb, was successfully carried out and sequenced. Alignment result by using MEGA4 program showed that there had been missense mutations in the rpoB gene. It had two amino acids changes to rpoB protein, they were glutamic acid to aspartic acid at codon 418 and glutamine to arginine at codon 510.